Effect of Whole-Body Vibration Exposure in Vehicles on Static Standing Balance after Riding - Junya Tatsuno; Setsuo Maeda (Vibration, 2023)
This study aims to investigate the effects of whole-body vibration (WBV) exposure on the disturbance of standing balance function assuming that the cause of slip, trip and fall accidents in the land transportation industry is related to WBV exposure when traveling in vehicles. In the experiment, ten participants underwent 60 min of virtual driving in a driving simulator (DS) for WBV exposure. In addition, standing balance measurements were conducted before exposure, immediately after exposure, 2 min after exposure and 4 min after exposure. Four conditions were considered by combining two magnitudes of WBV exposure and the driver and passenger conditions. This study focused on two indexes of standing balance, namely, total length and enveloped area and the rate of change relative to the value before the vibration exposure was calculated. The rate of change remained almost constant at 1.0 in the control condition without vibration exposure, whereas that under vibration exposure conditions varied. Interestingly, the rate of change at 2 min after exposure remained high in the driver condition, but it decreased to almost 1.0 in the passenger condition. Since no difference appeared in the vibration acceleration measured at the seating surface between the driver and passenger conditions, it was believed that the difference between the driving and passenger conditions was related to fatigue caused by the accelerator-pedal operation. As a result of considering the percentage of the standing balance that returned to 1.0 after 4 min in most conditions, this study proposed that a rest period of several minutes be allowed from the experiment in which the participants were exposed to vibration at <semantics>0.5<mspace width="0.166667em"></mspace>m/s2</semantics> rms for 60 min at the DS. Further basic experiments will be conducted to introduce another WBV exposure assessment, including loss of standing balance as a health indicator, to ISO 2631-1.